Adult extrarenal teratoid Wilms’ tumor: A case report and review of literature - Linhong Liao; Hui Cheng (Indian Journal of Pathology and Microbiology)
A 19-year-old woman presented with painless lower abdominal discomfort and a cystic-solid mass measuring 15.9 cm on the right ovary. She subsequently underwent laparoscopic right ovarian cystectomy. Microscopic examination of the mass showed the typical morphological features of Wilms’ tumor and the predominance of teratoid elements constituting more than 50% of the tumor. To date, few cases of extrarenal teratoid Wilms’ tumor (TWTs) in adults have been reported in the literature. The case presented in the present is the third reported case of adult extrarenal TWT occurring in ovary.